An insight into the first stages of the Ferrar magmatism: ultramafic cumulates from Harrow Peaks, northern Victoria Land, Antarctica - Pelorosso, Beatrice; Bonadiman, Costanza; Ntaflos, Theodoros; Gregoire, Michel; Gentili, Silvia; ZANETTI, Alberto; Coltorti, Massimo (Contributions to Mineralogy and Petrology, 2019)
A group of ultramafic xenoliths hosted in Cenozoic hypabyssal rocks from Harrow Peaks (northern Victoria Land, Antarctica) show textural and geochemical features far removed from anything previously observed in mantle xenoliths of this region and elsewhere in Antarctica. They consist of spinel-bearing lherzolites and harzburgites, characterised by a predominant equigranular texture with orthopyroxene modal contents remarkably higher in lherzolites (18–26 volume%) with respect to the harzburgite (13 vol%), one orthopyroxenite, and three composite xenoliths. The latter are formed by an olivine-dominant assemblage (olivine > 70%) crosscut by large monomineralic (amphibole or clinopyroxene) or bimineralic (amphibole + clinopyroxene) veins. No significant correlation was observed between the lithology and the Fo content (90.21–82.81) of olivine, suggesting that these rocks could be derived from a cumulus process. The presence of the orthopyroxenite suggests that the inferred melt/s from which they stemmed was close (or even above) to silica saturation. Based on major and trace-element mineral/melt and mineral/mineral equilibrium modelling, these rocks were formed by progressive extraction of olivine from a high magnesium (Mg = 72)—high temperature (~ 1300°C) melt following a very short fractionation line. Thermobarometric results indicate the stationing of Harrow Peaks cumulates in the P field of 1.3 ± 0.2 (dunites)—0.5 ± 0.2 (orthopyroxenite)GPa. These values well match the crust/mantle boundary (Moho) of the region. The combined geochemical and petrological data suggest that Harrow Peaks melts could be related to the initial stage of the Jurassic Ferrar magmatism, whose deep cumulates were subsequently affected by the Cenozoic alkaline metasomatism, widely detected in the northern Victoria Land lithosphere and responsible for the formation of the late amphibole/amphibole + clinopyroxene veins.